Fixation strength of a polyetheretherketone femoral component in total knee arthroplasty. (November 2017) - de Ruiter, Lennert; Janssen, Dennis; Briscoe, Adam; Verdonschot, Nico
Highlights: Pull-off fixation experiment for PEEK femoral cemented TKA implants. Smooth PEEK bonding surfaces do not provide sufficient adhesion. Adding macro- and microtexture improves fixation significantly. Fixation strength of PEEK is in the range of incumbent devices. PEEK replicates the main failure mechanism of CoCr. Abstract: Introduction: Introducing polyetheretherketone (PEEK) polymer as a material for femoral components in total knee arthroplasty (TKA) could potentially lead to a reduction of the cemented fixation strength. A PEEK implant is more likely to deform under high loads, rendering geometrical locking features less effective. Fixation strength may be enhanced by adding more undercuts or specific surface treatments. The aim of this study is to measure the initial fixation strength and investigate the associated failure patterns of three different iterations of PEEK-OPTIMA ® implants compared with a Cobalt–Chromium (CoCr) component. Methods: Femoral components were cemented onto trabecular bone analogue foam blocks and preconditioned with 86, 400 cycles of compressive loading (2600 N–260 N at 1 Hz). They were then extracted while the force was measured and the initial failure mechanism was recorded. Four groups were compared: CoCr, regular PEEK, PEEK with an enhanced cement-bonding surface and the latter with additional surface primer. Results: The mean pull-off forces for the four groups were 3814 N, 688 N, 2525 N and 2552 N, respectively. The initial failure patterns for groups 1, 3 and 4 were the same; posterior condylar foam fracture and cement–bone debonding. Implants from group 2 failed at the cement–implant interface. Conclusions: This study has shown that a PEEK-OPTIMA ® femoral TKA component with enhanced macro- and microtexture is able to replicate the main failure mechanism of a conventional CoCr femoral implant. The fixation strength is lower than for a CoCr implant, but substantially higher than loads occurring under in-vivo conditions. Graphical abstract: